PREDICTION MODEL FOR DETERMINING IMPORTANT FACTORS OF SUCCESS OF EXTERNAL CEPHALIC VERSION - Arif, Wasima; Maqsood, Fauzia; Iqbal, Marryam; Khanum, Zohra; Lodhi, Sohail Khursheed; Ghias, Muhammad (Journal of Ayub Medical College Abbottabad, 2012)
Background: The External cephalic version (ECV) is a skill as well as an art that could be easily acquired. It has become a valuable option in the management of breech foetus at term. Aims of this study were to determining those factors that were significantly associated with success of external cephalic version (ECV) procedure. Method: This prospective interventional study was conducted at Department of Obstetrics and Gynaecology, Unit-III, Services Hospital, Lahore, Pakistan from July 2007 to December 2009. Total of 56 patients who had undergone ECV was analysed descriptively and analytically. Univariate and multivariate data analysis was performed. Pre-procedural factors (gravidity, gestational age, amniotic fluid index, placental location, type of breech, maternal obesity, foetal weight), and factors associated with the procedure itself (abdominal wall musculature tone, uterine tone, maternal anxiety, maternal threshold for pain, engagement of breech, number of attempts) were assessed. Results: Thirty-three patients were successfully converted to vertex presentation. In multivariate analysis, placenta, type of breach, station of breach and number of attempts (‰¤2 times) were significantly associated factors with ECV procedure. Conclusion: ECV is most likely to succeed when the patient has already one pregnancy and child birth, the breech is not engaged, and is flexed. Procedure is usually successful within one or two attempts, whereas ongoing attempts lead to increased maternal anxiety, lesser cooperation and ending in failure. Keywords: External cephalic version (ECV), breech